2007
DOI: 10.1007/s11103-006-9122-y
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of a conifer Abscisic Acid Insensitive3 transcription factor induces high-level synthesis of recombinant human α-l-iduronidase in transgenic tobacco leaves

Abstract: We are examining various plant-based systems to produce enzymes for the treatment of human lysosomal storage disorders. Constitutive expression of the gene encoding the human lysosomal enzyme, alpha-L-iduronidase (IDUA; EC 3.2.1.76) in leaves of transgenic tobacco plants resulted in low-enzyme activity, and the protein appeared to be subject to proteolysis. Toward enhancing production of this recombinant enzyme in vegetative tissues, transgenic tobacco plants were generated to co-express a CaMV35S:Chamaecypari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Characterization of the gymnosperm ABI3 in both yellow-cedar, and in heterologous (angiosperm) hosts, shows that the CnABI3 protein has similar roles as its angiosperm counterparts. [1][2][3] As reported in a recent publication, using a yeast 2-hybrid approach, 4 we further identified a new protein of yellow-cedar, CnAIP2, that interacts with CnABI3. CnAIP2 plays important roles during several key transitions of the plant lifecycle, and this protein appears to act as a global regulator with functions opposite to those of ABI3 proteins.…”
supporting
confidence: 60%
“…Characterization of the gymnosperm ABI3 in both yellow-cedar, and in heterologous (angiosperm) hosts, shows that the CnABI3 protein has similar roles as its angiosperm counterparts. [1][2][3] As reported in a recent publication, using a yeast 2-hybrid approach, 4 we further identified a new protein of yellow-cedar, CnAIP2, that interacts with CnABI3. CnAIP2 plays important roles during several key transitions of the plant lifecycle, and this protein appears to act as a global regulator with functions opposite to those of ABI3 proteins.…”
supporting
confidence: 60%
“…Indeed, particularly relevant to this study, our previous research showed that yellow cedar CnABI3 functions nearly perfectly in the Arabidopsis ABI3 null mutant abi3-6, restoring almost all of the mutant's severe phenotypes (Zeng and Kermode, 2004). Furthermore, ectopic expression of the conifer CnABI3 gene in transgenic tobacco (Nicotiana tabacum) activates the promoters of seed storage protein genes, similar to that of the Arabidopsis ABI3 gene (Zeng et al, 2003;Kermode et al, 2007). Thus, due to the severe limitations of conventional approaches for the functional characterization of conifer genes/proteins (i.e.…”
Section: A General Note Regarding the Experimental Systems Of This Rementioning
confidence: 72%
“…Plants also have high-fidelity expression, folding and post-translational modification mechanisms, which could produce human proteins of substantial structural and functional equivalency compared to proteins from mammalian expression systems (Gomord andFaye 2004, Joshi andLopez 2005). Additionally, plant-made human proteins of clinical interest (Schillberg et al 2005, Twyman et al 2005, Vitale and Pedrazzini 2005, Tiwari et al 2009, such as antibodies (Hassan et al 2008, Ko et al 2009, De Muynck et al 2010, Lai et al 2010, vaccines (Hooper 2009, Alvarez andCardineau 2010), cytokines (Elias-Lopez et al 2008) and enzymes (Kermode et al 2007, Stein et al 2009, are free of potentially hazardous human diseases, viruses or bacterial toxins. However, there is considerable concern regarding the potential hazards of contamination of the natural gene pool by the transgenes and possible additional safety precautions will raise the production cost.…”
Section: Transgenic Plantsmentioning
confidence: 99%